PGAM5-mediated programmed necrosis of hepatocytes drives acute liver injury - He, Gui-Wei; Günther, Claudia; Kremer, Andreas; Thonn, Veronika; Amann, Kerstin Ute; Poremba, Christopher; Neurath, Markus; Wirtz, Stefan; Becker, Christoph (Gut, 2016)
Autoimmune hepatitis (AIH) is a severe necroinflammatory liver disease associated with significant mortality. Although loss of hepatocytes is generally recognised as a key trigger of liver inflammation and liver failure, the regulation of hepatic cell death causing AIH remains poorly understood. The aim of this study was to identify molecular mechanisms that drive hepatocyte cell death in the pathogenesis of acute liver injury.Acute liver injury was modelled in mice by intravenous administration of concanavalin A (ConA). Liver injury was demonstrated by serum transaminases and histological assessment of liver sections. PGAM5-deficient mice (PGAM5-/-) were used to determine its role in experimental hepatitis. Mdivi-1 was used as an inhibitor of dynamin-related protein 1 (Drp1)-mediated mitochondrial fission. Mitochondrial fission and the expression of PGAM5 were compared between liver biopsies derived from patients with AIH and control patients.PGAM5 was highly expressed in hepatocytes of patients with AIH and in mice with ConA-induced experimental hepatitis. Deficiency of PGAM5 protected mice from ConA-induced hepatocellular death and liver injury. PGAM5 regulated ConA-induced mitochondrial fission in hepatocytes. Administration of the Drp1-inhibitor Mdivi-1 blocked mitochondrial fission, diminished hepatocyte cell death and attenuated liver tissue damage induced by ConA.Our data demonstrate for the first time that PGAM5 plays an indispensable role in the pathogenesis of ConA-induced liver injury. Downstream of PGAM5, Drp1-mediated mitochondrial fission is an obligatory step that drives the execution of hepatic necrosis and tissue damage. Our data highlight the PGAM5-Drp1 axis as a potential therapeutic target for acute immune-mediated liver injury.
EVALuna2:2219